Method for synthesizing aliphatic polycarbonate by ester exchange method and aliphatic polycarbonate

By using co-hydrolyzed products of titanate and other compounds as catalysts, the APC products of aliphatic polycarbonate were improved by transesterification, solving the problems of low molecular weight and poor mechanical properties, and achieving APC products with high molecular weight and excellent properties.

CN119875098APending Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311378320.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing APC products synthesized aliphatic polycarbonate by transesterification methods have low molecular weight, poor mechanical properties, and long reaction time during the preparation process, which has failed to effectively solve the problems of low molecular weight and poor strength.

Method used

The co-hydrolyzed product of titanate and other compounds is used as the transesterification catalyst and polycondensation catalyst, and high molecular weight APC products are prepared through feed heating, transesterification reaction, polycondensation reaction and discharge steps.

Benefits of technology

It improves the molecular weight of APC products, which can be as high as 1.1×105, improves mechanical properties, shortens the esterification and polycondensation reaction time, and has white color and excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004508652790000151
    Figure BDA0004508652790000151
Patent Text Reader

Abstract

According to the method, carbonic ester and aliphatic dihydric alcohol are used as raw materials, a transesterification catalyst and a polycondensation catalyst are added according to steps, and the aliphatic polycarbonate is prepared through the steps of feeding, heating, transesterification, polycondensation and discharging. According to the method, co-hydrolysis products of titanate and other compounds are respectively used as transesterification and polycondensation catalysts, so that the defects of long reaction time and low molecular weight of the product in the conventional transesterification method are overcome, the prepared aliphatic polycarbonate product has high molecular weight, the number-average molecular weight is 2 * 10 < 4 >-1.1 * 10 < 5 >, and the white and hue b value of the product is 3-6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of synthesis of biodegradable aliphatic polycarbonate, in particular to a method for synthesizing aliphatic polycarbonate by ester exchange and the aliphatic polycarbonate. Background Art

[0002] Aliphatic polycarbonate (APC) has excellent biodegradability, biocompatibility, gas barrier properties, excellent light transmittance, anti-fog and hydrolysis resistance, and excellent thermodynamic properties. Compared with aromatic polycarbonate (PC), the molecular chain of APC is more flexible, so its glass transition temperature is lower, thermal stability and mechanical properties are poor, which limits its application. In recent years, with the improvement of people's living standards and the enhancement of environmental protection awareness, biodegradable APC has received increasing attention. APC is a type of surface-soluble biodegradable polymer material, which can be completely degraded into neutral diols and CO2 through reactions such as hydrolysis or alcoholysis. It has good biocompatibility and biodegradability, and there are many varieties. By adjusting the main chain chemical structure, it can have a wide range of physical, chemical and biological properties to meet the needs of different fields. Compared with biodegradable aliphatic polyesters, APC does not produce small molecule acidic substances during the degradation process, so it will not cause adverse reactions such as tissue inflammation, and has better storage stability. It has good application prospects in medical materials, pharmaceutical materials, packaging, agricultural mulch films and other fields.

[0003] The synthesis methods of APC usually include phosgene method, ring-opening polymerization method, carbon dioxide / epoxide copolymerization and ester exchange method. The phosgene method is a method for preparing APC by solution polycondensation of phosgene and diols. The yield is low, phosgene is highly toxic, and the production conditions are harsh. It is rarely used now. The ring-opening polymerization method is a method for preparing APC by ring-opening polymerization of cyclic carbonates. The reaction conditions are very harsh, such as high-purity monomers and a strict anhydrous and oxygen-free system. This method is currently only in the laboratory research stage. The CO2 / epoxide copolymerization method is a method for preparing APC by copolymerizing CO2 and epoxides. There are still many problems in the preparation process. The ester exchange method is a method for preparing APC by ester exchange between carbonates and aliphatic diols. The structural properties of APC can be controlled by adjusting the type of diols. The process route is simple, green and environmentally friendly, and has good industrial prospects.

[0004] There are related methods for synthesizing aliphatic polycarbonate APC by ester exchange, but the prepared APC products have low molecular weight and poor mechanical properties, or the catalyst or method used in the preparation process still has defects, the reaction time is long, and the product performance still does not meet the use requirements. For example: Patents CN 101643542A, CN 10038489C, CN 113402704A, etc. These disclosed methods have not effectively solved the defects of low molecular weight and poor strength of the prepared APC, and the mechanical properties are poor in the subsequent processing process, resulting in inapplicability.

[0005] Patent CN 101643542A discloses a method for preparing a high molecular weight aliphatic polycarbonate, which comprises the steps of carrying out an ester exchange reaction between a diol and a carbonate under the action of a catalyst (e.g., potassium hydroxide, etc.) and heating, removing methanol in the reaction, and adding a catalyst (e.g., antimony trioxide, etc.) to the prepolymer for vacuum polycondensation to obtain a product. The obtained product is a crystalline solid with a low molecular weight. The ester exchange and polycondensation reaction time is very long. For example, in the embodiment, the polycondensation reaction takes 12 hours to obtain a product with a molecular weight of only 60700. Under the condition of a short reaction time, the molecular weight of the prepared product is much lower than that of polybutylene terephthalate-co-adipate (PBAT), polybutylene succinate (PBS), etc., which are currently used as biodegradable materials, and thus the mechanical properties are poor.

[0006] Patent CN 10038489C discloses a method for preparing aliphatic oligocarbonate diols, which relates to an improved method for preparing aliphatic oligocarbonate diols by ester exchange reaction of dimethyl carbonate (DMC) and aliphatic diols. The number average molecular weight of the product is 500-5000 g / mol. Obviously, the molecular weight of the product of this ester exchange method is too low.

[0007] Patent CN 113402704A discloses a polycarbonate copolymer and its preparation method and use. The method is to introduce sulfonic acid aliphatic polycarbonate into polycarbonate chain segments by copolymerization, thereby improving the compatibility and fluidity of conventional polycarbonate. This method of improving performance is to introduce aromatic groups into specific sulfonic acid aliphatic polycarbonate. The preparation method and raw materials are specific and are not suitable for the preparation process of synthesizing aliphatic polycarbonate by conventional ester exchange method. Summary of the invention

[0008] In order to solve the problems existing in the above prior art, the present invention provides a method for preparing aliphatic polycarbonate (APC for short) by ester exchange method, which is used for preparing high molecular weight APC products. Carbonate and aliphatic diol are used as raw materials, and a high-efficiency ester exchange catalyst and a polycondensation catalyst are added step by step. The APC product is prepared through the steps of adding materials, heating, ester exchange reaction, polycondensation reaction, and discharging. The ester exchange catalyst and polycondensation catalyst are co-hydrolysis products of titanate and other compounds.

[0009] One of the purposes of the present invention is to provide a method for synthesizing aliphatic polycarbonate by ester exchange, comprising carrying out an ester exchange reaction with carbonate and aliphatic diol as raw materials in the presence of an ester exchange catalyst, and carrying out a condensation reaction of the obtained ester exchange intermediate product in the presence of a condensation catalyst to obtain the aliphatic polycarbonate.

[0010] In the above technical solution, the carbonate is at least one of dimethyl carbonate, diethyl carbonate, and dipropyl carbonate, and the aliphatic diol is at least one of ethylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.

[0011] In the above technical solution, the ester exchange catalyst is a co-hydrolysis product of titanate and orthosilicate. Preferably, the titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and the orthosilicate is at least one of methyl orthosilicate, ethyl orthosilicate, and propyl orthosilicate.

[0012] The transesterification catalyst can be obtained by a conventional hydrolysis method, and can be specifically prepared according to the following steps: titanate and orthosilicate are prepared by hydrolysis and drying at room temperature, wherein the molar ratio of titanium to silicon (Ti / Si) in the transesterification catalyst is 5:1 to 10:1, preferably 5:1 to 9:1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 and any parameter range between any two of the above values.

[0013] In the above technical solution, the condensation catalyst is a co-hydrolysis product of a titanate and an acetate. Preferably, the titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate; and the acetate is at least one of sodium acetate, magnesium acetate, zinc acetate, and manganese acetate.

[0014] The polycondensation catalyst can be obtained by a conventional hydrolysis method, and can be specifically prepared according to the following steps: titanate and acetate are hydrolyzed and dried at room temperature under neutral or alkaline conditions, wherein the molar ratio (Ti / M) of titanium in the polycondensation catalyst and metal element M in the acetate is 1:1 to 10:1, preferably 2:1 to 10:1, for example, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1 and any parameter range between any two of the above values.

[0015] In the above technical solution, the molar ratio of carbonate to aliphatic diol is 1:(1-10), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 and any parameter range between any two of the above values.

[0016] The transesterification reaction conditions in the above technical solution include: temperature of 110-200°C, pressure of 0-0.2MPa (gauge pressure), and time of 1-3 hours; preferably, temperature of 120-190°C, pressure of 0-0.15MPa (gauge pressure). Specifically, the temperature can be 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 180°C, 200°C, and any parameter range between any two of the above values.

[0017] The molar ratio of the transesterification catalyst to the carbonate is 1×10 -5 ~1×10 -3 , preferably 5×10 -5 ~5×10 -4 , wherein the amount of the transesterification catalyst is calculated based on the titanium element contained.

[0018] The polycondensation reaction conditions in the above technical solution include: temperature of 200-260°C, pressure of 40-300 Pa (absolute pressure), and time of 1-3 hours; preferably, temperature of 210-250°C, and pressure of 50-200 Pa (absolute pressure). Specifically, the temperature can be 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, and any parameter range between any two of the above values.

[0019] The molar ratio of the polycondensation catalyst to the carbonate is 1×10 -5 ~1×10 -3 , preferably 5×10 -5 ~5×10 -4 , wherein the amount of the polycondensation catalyst is calculated based on the titanium element contained.

[0020] According to a preferred embodiment of the present invention, the method for synthesizing aliphatic polycarbonate by ester exchange comprises:

[0021] A1: In the heating stage, the reactor is filled with nitrogen, carbonate and aliphatic diol are weighed in proportion and put into the reactor, and an ester exchange catalyst is added, and the temperature is raised from room temperature to 110-200°C;

[0022] A2 ester exchange reaction stage, the ester exchange reaction is carried out under the conditions of controlling the temperature to 110-200°C and the pressure to 0-0.2MPa (gauge pressure) for 1-3 hours, and the small molecule liquid is distilled to reach more than 95% of the theoretical value, and the reaction is completed to obtain the ester exchange intermediate product;

[0023] A3 polycondensation reaction stage, adding a polycondensation catalyst to the ester exchange intermediate product, controlling the temperature to 200-260° C. and the pressure to 40 Pa-300 Pa (absolute pressure) to carry out the polycondensation reaction for 1-3 hours to obtain a polycondensation product;

[0024] In the A4 discharging stage, after the polycondensation reaction is completed, the material is discharged, water-cooled, cast into strips, and pelletized to obtain aliphatic polycarbonate APC products.

[0025] A second object of the present invention is to provide an aliphatic polycarbonate obtained by the above method.

[0026] In the above technical solution, the number average molecular weight of the aliphatic polycarbonate is 2×10 4 ~1.1×10 5 , the hue b value is 3 to 6.

[0027] The beneficial effects of the present invention are:

[0028] The preparation method of APC by ester exchange method of the present invention comprises the following steps: before ester exchange reaction and polycondensation reaction, co-hydrolysis products of titanate and other compounds are added as ester exchange catalyst and polycondensation catalyst respectively to prepare APC product, that is, the molecular weight of the product can be improved by simply prolonging the polycondensation reaction time, or by appropriately increasing the amount of catalyst without prolonging the polycondensation reaction time; and the product has good hue and a hue b value of 3-6, which fully meets the requirements for molecular weight and hue when the product is used.

[0029] The molecular weight of the APC product prepared by the present invention can be as high as 1.1×10 5 , which solves the defect of low molecular weight of APC products prepared by the previous ester exchange method and solves the problem of poor mechanical properties of APC products during processing and subsequent applications.

[0030] The APC product prepared by the present invention has good biodegradability, can be completely degraded into harmless small molecules in nature and does not produce small molecule acidic substances, and can be widely used in the fields of medical materials, pharmaceutical materials, packaging and agricultural mulch films.

[0031] The preparation method of APC by ester exchange provided by the present invention has achieved the following beneficial results compared with the existing preparation method: a product with higher molecular weight is prepared compared with the existing method for preparing APC by ester exchange, and the increase in molecular weight improves its mechanical properties; the esterification and polycondensation reaction time is significantly shortened, and the reaction efficiency is improved; the prepared APC product has white hue and good performance. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0033] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0034] In each embodiment and comparative example of the present invention, each performance data is tested according to the following test method:

[0035] The molecular weight and distribution of APC products are determined by gel chromatography (GPC). The molecular weight Mn is the number average molecular weight, and Mw is the weight average molecular weight. The instrument specification is Waters 1515. The test conditions are: the mobile phase is chloroform, the flow rate is 1 ml / min, and the temperature is 35°C.

[0036] The hue b value of APC products is measured using a TC-PⅡG fully automatic colorimeter.

[0037] Example 1-Example 8 Preparation of APC:

[0038] The transesterification catalyst and the polycondensation catalyst are prepared by hydrolyzing and drying the respective raw materials under neutral or alkaline conditions at room temperature.

[0039] Example 1

[0040] Main dosage conditions:

[0041] (1) Transesterification catalyst C1, tetrabutyl titanate / ethyl orthosilicate, Ti / Si=5:1, the two components are calculated by the ratio of the amount of Ti and Si contained (the same below);

[0042] (2) Polycondensation catalyst S1, tetrabutyl titanate / sodium acetate, Ti / Na=1:1, the two components are calculated by the ratio of the amount of Ti and Na contained (the same below).

[0043] Preparation process:

[0044] In step A1, 90 g (1 mol) of dimethyl carbonate and 62 g (1 mol) of ethylene glycol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and 1×10 -3 mol, dosage conditions: C1 / dimethyl carbonate = 1×10 -3 , the catalyst C1 is calculated based on the molar amount of the titanium element (the same below), stirred evenly, and heated from room temperature to 110°C;

[0045] Step A2, the esterification reaction is carried out for 3 hours under the conditions of controlling the temperature to 110° C. and the pressure to 0 (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0046] In step A3, the amount of polycondensation catalyst S1 added to the ester exchange intermediate product is 1×10 -3 mol, catalyst S1 is calculated based on the molar amount of titanium element (the same below), and the dosage condition is: S1 / dimethyl carbonate = 1×10 -3 , stirring evenly, controlling the temperature to 200°C and the pressure to 40Pa (absolute pressure) for 3 hours, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0047] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0048] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0049] Example 2

[0050] Main dosage conditions:

[0051] (1) Transesterification catalyst C2, tetraisopropyl titanate / propyl orthosilicate, Ti / Si=5:1;

[0052] (2) Polycondensation catalyst S2, tetramethyl titanate / magnesium acetate, Ti / Mg=1:1.

[0053] Preparation process:

[0054] In step A1, 90 g (1 mol) of dimethyl carbonate and 620 g (10 mol) of ethylene glycol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and 1×10 -5 mol, dosage conditions: C2 / dimethyl carbonate = 1×10 -5 , stir evenly, and heat from room temperature to 200°C;

[0055] Step A2, the esterification reaction is carried out for 1 hour under the conditions of controlling the temperature to 200° C. and the pressure to 0.2 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0056] In step A3, the amount of polycondensation catalyst S2 added to the ester exchange intermediate product is 1×10 -5 mol, dosage conditions: S2 / dimethyl carbonate = 1×10 -5 , stirring evenly, controlling the temperature to 260°C and the pressure to 40Pa (absolute pressure) for 3 hours, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0057] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0058] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0059] Example 3

[0060] Main dosage conditions:

[0061] (1) Transesterification catalyst C3, tetrabutyl titanate / methyl orthosilicate, Ti / Si=10:1;

[0062] (2) Polycondensation catalyst S3, tetrabutyl titanate / zinc acetate, Ti / Zn=1:1.

[0063] Preparation process:

[0064] In step A1, 118 g (1 mol) of diethyl carbonate and 180 g (2 mol) of 1,4-butanediol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and 1×10 -3 mol, dosage conditions: C3 / diethyl carbonate = 1×10 -3 , stir evenly, and heat from room temperature to 150°C;

[0065] Step A2, the esterification reaction is carried out for 3 hours under the conditions of controlling the temperature to 150° C. and the pressure to 0.1 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0066] In step A3, the amount of polycondensation catalyst S3 added to the ester exchange intermediate product is 1×10 -3 mol, dosage conditions: S3 / diethyl carbonate = 1×10 -3 , stirring evenly, controlling the temperature to 260°C and the pressure to 40Pa (absolute pressure) for 1 hour, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0067] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0068] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0069] Example 4

[0070] Main dosage conditions:

[0071] (1) Transesterification catalyst C4, tetraisopropyl titanate / ethyl orthosilicate, Ti / Si=10:1;

[0072] (2) Polycondensation catalyst S4, tetraethyl titanate / sodium acetate, Ti / Na=10:1.

[0073] Preparation process:

[0074] In step A1, 118 g (1 mol) of diethyl carbonate and 270 g (3 mol) of 1,4-butanediol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and 5×10 -5 mol, dosage conditions: C4 / diethyl carbonate = 5×10 -5 , stir evenly, and heat from room temperature to 150°C;

[0075] Step A2, the esterification reaction is carried out for 1 hour under the conditions of controlling the temperature to 150° C. and the pressure to 0.1 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0076] In step A3, the amount of polycondensation catalyst S4 added to the ester exchange intermediate product is 1×10 -4 mol, dosage conditions: S4 / diethyl carbonate = 1×10 -4 , stirring evenly, controlling the temperature to 230°C and the pressure to 300 Pa (absolute pressure) for condensation polymerization for 3 hours, and stopping the reaction after reaching the required stirring power to obtain a condensation polymerization product;

[0077] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0078] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0079] Example 5

[0080] Main dosage conditions:

[0081] (1) Transesterification catalyst C5, tetramethyl titanate / ethyl orthosilicate, Ti / Si=9:1;

[0082] (2) Polycondensation catalyst S5, tetraisopropyl titanate / zinc acetate, Ti / Zn=9:1.

[0083] Preparation process:

[0084] In step A1, 146 g (1 mol) of dipropyl carbonate and 312 g (3 mol) of 1,5-pentanediol were weighed and put into a reactor, nitrogen was filled in for replacement, and 1×10 -4 mol, dosage conditions: C5 / dipropyl carbonate = 1×10 -4 , stir evenly, and heat from room temperature to 200°C;

[0085] Step A2, the esterification reaction is carried out for 1 hour under the conditions of controlling the temperature to 200° C. and the pressure to 0.2 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0086] In step A3, the amount of polycondensation catalyst S5 added to the ester exchange intermediate product is 1×10 -4 mol, dosage condition: S5 / dipropyl carbonate = 1×10 -4 , stirring evenly, controlling the temperature to 260°C and the pressure to 300 Pa (absolute pressure) for 3 hours, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0087] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0088] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0089] Example 6

[0090] Main dosage conditions:

[0091] (1) Transesterification catalyst C6, tetraethyl titanate / ethyl orthosilicate, Ti / Si=8:1;

[0092] (2) Polycondensation catalyst S6, tetrabutyl titanate / magnesium acetate, Ti / Mg=5:1.

[0093] Preparation process:

[0094] In step A1, 146 g (1 mol) of dipropyl carbonate and 590 g (5 mol) of 1,6-hexanediol were weighed and put into a reactor, nitrogen was filled in for replacement, and 1×10 -5 mol, dosage conditions: C6 / dipropyl carbonate = 1×10 -5 , the catalyst C1 is calculated based on the molar amount of the titanium element (the same below), stirred evenly, and heated from room temperature to 110° C. under the condition of a reaction pressure of 0 (gauge pressure);

[0095] Step A2, the esterification reaction is carried out for 3 hours under the conditions of controlling the temperature to 110° C. and the pressure to 0 (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0096] In step A3, the amount of polycondensation catalyst S6 added to the ester exchange intermediate product is 1×10 -3 mol, dosage condition: S6 / dipropyl carbonate = 1×10 -3 , stirring evenly, controlling the temperature to 260°C and the pressure to 40Pa (absolute pressure) for 1 hour, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0097] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0098] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0099] Example 7

[0100] Main dosage conditions:

[0101] (1) Transesterification catalyst C7, tetramethyl titanate / methyl orthosilicate, Ti / Si=10:1;

[0102] (2) Polycondensation catalyst S7, tetraethyl titanate / manganese acetate, Ti / Mn=1:1.

[0103] Preparation process:

[0104] In step A1, 90 g (1 mol) of dimethyl carbonate and 590 g (5 mol) of 1,6-hexanediol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and 1×10 -3 mol, dosage conditions: C7 / dimethyl carbonate = 1×10 -3 , stir evenly, and heat from room temperature to 110°C;

[0105] Step A2, the esterification reaction is carried out for 1 hour under the conditions of controlling the temperature to 110° C. and the pressure to 0 (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0106] In step A3, the amount of polycondensation catalyst S7 added to the ester exchange intermediate product is 1×10 -4 mol, dosage condition: S7 / dimethyl carbonate = 1×10 -4 , stirring evenly, controlling the temperature to 200°C and the pressure to 40Pa (absolute pressure) for 1 hour, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0107] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0108] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0109] Example 8

[0110] Main dosage conditions:

[0111] (1) Transesterification catalyst C8, tetraethyl titanate / ethyl orthosilicate, Ti / Si=5:1;

[0112] (2) Condensation polymerization catalyst S8, tetraisopropyl titanate / manganese acetate, Ti / Mn=5:1.

[0113] Preparation process:

[0114] In step A1, 118 g (1 mol) of diethyl carbonate and 900 g (10 mol) of 1,4-butanediol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and 1×10 -5 mol, dosage conditions: C8 / diethyl carbonate = 1×10 -5 , stir evenly, and heat from room temperature to 200°C;

[0115] Step A2, the esterification reaction is carried out for 3 hours under the conditions of controlling the temperature to 200° C. and the pressure to 0.2 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0116] In step A3, the amount of polycondensation catalyst S8 added to the ester exchange intermediate product is 1×10 -4 mol, dosage condition: S8 / diethyl carbonate = 1×10 -4, stirring evenly, controlling the temperature to 230° C. and the pressure to 100 Pa (absolute pressure) for 2 hours, stopping the reaction after reaching the required stirring power, and obtaining a condensation product;

[0117] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain APC products.

[0118] The molecular weight and hue b value of the prepared APC product were tested, and the results are listed in Table 1 below.

[0119] Comparative Example 1 Preparation of APC

[0120] Preparation process:

[0121] In step A1, 90 g (1 mol) of dimethyl carbonate and 62 g (1 mol) of ethylene glycol were weighed and put into a reactor, nitrogen was filled into the reactor for replacement, and potassium hydroxide (KOH) from an existing method (patent CN 101643542A) was added as an ester exchange catalyst C0 in an amount of 1×10 -3 mol, dosage condition: C0 / dimethyl carbonate = 1×10 -3 , stir evenly, and heat from room temperature to 110°C;

[0122] Step A2, the esterification reaction is carried out for 3 hours under the conditions of controlling the temperature to 110° C. and the pressure to 0 (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0123] In step A3, antimony trioxide (Sb2O3) from an existing method (patent CN101643542A) is added to the ester exchange intermediate product as a polycondensation catalyst S0 in an amount of 1×10 -3 mol, dosage condition: S0 / dimethyl carbonate = 1×10 -3 , stirring evenly, controlling the temperature to 200° C. and the pressure to 40 Pa (absolute pressure) for 3 hours to obtain a condensation product;

[0124] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain an APC product. The molecular weight and hue b value thereof are tested, and the results are listed in Table 1.

[0125] Comparative Example 2 Preparation of APC

[0126] Preparation process:

[0127] In step A1, 90 g (1 mol) of dimethyl carbonate and 620 g (10 mol) of ethylene glycol were weighed and put into a reaction kettle, and nitrogen was filled into the reaction kettle for replacement. Lithium acetate from the existing method (Example 5 of Patent CN 101643542A) was added as an ester exchange catalyst in an amount of 1×10-5 mol, dosage conditions: lithium acetate / dimethyl carbonate = 1×10 -5 , stir evenly, and heat from room temperature to 200°C;

[0128] Step A2, the esterification reaction is carried out for 1 hour under the conditions of controlling the temperature to 200° C. and the pressure to 0.2 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0129] In step A3, tetraisopropyl titanate from the prior art (Example 5 of patent CN101643542A) is added to the ester exchange intermediate product as a polycondensation catalyst in an amount of 1×10 -5 mol, dosage conditions: tetraisopropyl titanate / dimethyl carbonate = 1×10 -5 , stirring evenly, controlling the temperature to 260° C. and the pressure to 40 Pa (absolute pressure) for condensation polymerization for 3 hours to obtain a condensation polymerization product;

[0130] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain an APC product. The molecular weight and hue b value thereof are tested, and the results are listed in Table 1.

[0131] Comparative Example 3 Preparation of APC

[0132] Preparation process:

[0133] In step A1, 118 g (1 mol) of diethyl carbonate and 180 g (2 mol) of 1,4-butanediol were weighed and put into a reaction kettle, and nitrogen was filled into the reaction kettle for replacement. Tetrabutyl titanate prepared in the prior art (Example 1 of Patent CN 101643542A) was added as an ester exchange catalyst in an amount of 1×10 -3 mol, dosage conditions: tetrabutyl titanate / diethyl carbonate = 1×10 -3 , stir evenly, and heat from room temperature to 150°C;

[0134] Step A2, the esterification reaction is carried out for 3 hours under the conditions of controlling the temperature to 150° C. and the pressure to 0.1 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0135] In step A3, the catalyst S3 (tetrabutyl titanate / zinc acetate Ti / Zn=1:1) in the above Example 3 is added to the ester exchange intermediate product as a polycondensation catalyst in an amount of 1×10 -3 mol, dosage conditions: S3 / diethyl carbonate = 1×10 -3 , stirring evenly, controlling the temperature to 260° C. and the pressure to 40 Pa (absolute pressure) for condensation reaction for 1 hour to obtain a condensation product;

[0136] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain an APC product. The molecular weight and hue b value thereof are tested, and the results are listed in Table 1.

[0137] Comparative Example 4 Preparation of APC

[0138] Preparation process:

[0139] In step A1, 118 g (1 mol) of diethyl carbonate and 270 g (3 mol) of 1,4-butanediol were weighed and put into a reactor, and nitrogen was introduced for replacement. The catalyst C4 (tetraisopropyl titanate / ethyl orthosilicate, Ti / Si=10:1) in the above Example 4 was used as an ester exchange catalyst in an amount of 5×10 -5 mol, dosage conditions: C4 / diethyl carbonate = 5×10 -5 , stir evenly, and heat from room temperature to 150°C;

[0140] Step A2, the esterification reaction is carried out for 1 hour under the conditions of controlling the temperature to 150° C. and the pressure to 0.1 MPa (gauge pressure), at which time the distillate reaches more than 95% of the theoretical value, the esterification reaction is completed, and an ester exchange intermediate product is obtained;

[0141] In step A3, lithium carbonate according to the existing method (Example 2 of patent CN101643542A) is added to the ester exchange intermediate product as a polycondensation catalyst in an amount of 1×10 -4 mol, dosage conditions: lithium carbonate / diethyl carbonate = 1×10 -3 , stirring evenly, controlling the temperature to 230° C. and the pressure to 300 Pa (absolute pressure) for condensation polymerization for 3 hours to obtain a condensation polymerization product;

[0142] In step A4, the liquid material is discharged, water-cooled, cast into bars, and pelletized to obtain an APC product. The molecular weight and hue b value thereof are tested, and the results are listed in Table 1.

[0143] Comparative Example 5 Preparation of Catalyst and APC by Direct Mixing Method

[0144] The catalyst component ratios in Example 8 are the same, except that the raw materials are not co-hydrolyzed but directly mixed as transesterification catalyst and polycondensation catalyst respectively:

[0145] (1) Transesterification Catalyst C 8混合 , tetraethyl titanate / ethyl orthosilicate, Ti / Si=5:1;

[0146] (2) Polycondensation catalyst S 8混合 , tetraisopropyl titanate / manganese acetate, Ti / Mn=5:1.

[0147] Preparation process: The same method as in Example 8 was used, with diethyl carbonate and 1,4-butanediol as raw materials, C 8混合 As transesterification catalyst, S 8混合 The prepared APC product was tested for molecular weight and hue b value as a polycondensation catalyst. The results are listed in Table 1 below.

[0148] Table 1 APC preparation experimental results

[0149]

[0150] As can be seen from Table 1, compared with Comparative Example 1, the APC products synthesized by using the co-hydrolyzed products as transesterification and polycondensation catalysts have a number average molecular weight Mn of 2×10 4 ~1.1×10 5 , good hue, and b value of 3 to 6; while the number average molecular weight Mn of APC synthesized using the existing method catalyst is only 7150, and the hue b value is 8.5.

[0151] Comparative Example 2 uses lithium acetate as an ester exchange catalyst and tetraisopropyl titanate as a condensation polymerization catalyst. The number average molecular weight Mn of the synthesized product is 7435, and the hue b value is 9.0, which is far inferior to Example 2. Example 2 uses exactly the same ester exchange and condensation polymerization reaction process conditions as Comparative Example 2.

[0152] Comparative Example 3 uses the polycondensation catalyst of the present invention and the ester exchange catalyst of the prior art. The number average molecular weight and hue b of the product are improved compared with those of Comparative Example 1, but are not as good as the product synthesized in Implementation 3 using exactly the same reaction process conditions.

[0153] Comparative Example 4 uses the ester exchange catalyst of the present invention and the condensation polymerization catalyst of the existing public technology. The number average molecular weight and hue b of the product are improved compared with those of Comparative Example 1, but are not as good as the product synthesized by Implementation 4 using the same reaction process conditions.

[0154] Comparative Example 5 adopts the catalyst component ratio of the present invention, does not adopt the co-hydrolysis method, and only adopts the direct mixing method as a catalyst to synthesize the APC product. Under the same synthesis process conditions, the number average molecular weight of the product is only about 50,000, while the number average molecular weight of the product using the co-hydrolysis method catalyst reaches 75,000, and the hue b value is not much different.

Claims

1. A method for synthesizing aliphatic polycarbonate by ester exchange, comprising carrying out an ester exchange reaction with carbonate and aliphatic diol as raw materials in the presence of an ester exchange catalyst, and carrying out a condensation reaction of the obtained ester exchange intermediate product in the presence of a condensation catalyst to obtain the aliphatic polycarbonate.

2. The method according to claim 1, characterized in that: The carbonate is at least one of dimethyl carbonate, diethyl carbonate and dipropyl carbonate; and / or, The aliphatic diol is at least one of ethylene glycol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; and / or, The molar ratio of the carbonate to the aliphatic diol is 1:(1-10).

3. The method according to claim 1, characterized in that: The transesterification catalyst is a co-hydrolysis product of a titanate and an orthosilicate. Preferably, the titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate, and the orthosilicate is at least one of methyl orthosilicate, ethyl orthosilicate, and propyl orthosilicate. Preferably, the molar ratio of titanium to silicon in the transesterification catalyst is 5:1 to 10:1, preferably 5:1 to 9:

1.

4. The method according to claim 1, characterized in that: The molar ratio of the transesterification catalyst to the carbonate is 1×10 -5 ~1×10 -3 , preferably 5×10 -5 ~5×10 -4 , wherein the amount of the transesterification catalyst is calculated based on the titanium element contained.

5. The method according to claim 1, characterized in that: The conditions of the transesterification reaction include: temperature of 110-200° C., pressure of 0-0.2 MPa (gauge pressure), and time of 1-3 hours; preferably, temperature of 120-190° C., pressure of 0-0.15 MPa (gauge pressure).

6. The method according to claim 1, characterized in that: The polycondensation catalyst is a co-hydrolysis product of a titanate and an acetate. Preferably, the titanate is at least one of tetramethyl titanate, tetraethyl titanate, tetraisopropyl titanate, and tetrabutyl titanate; and the acetate is at least one of sodium acetate, magnesium acetate, zinc acetate, and manganese acetate. Preferably, the molar ratio of titanium in the polycondensation catalyst to the metal element in the acetate is 1:1 to 10:1, preferably 2:1 to 10:

1.

7. The method according to claim 1, characterized in that: The molar ratio of the polycondensation catalyst to the carbonate is 1×10 -5 ~1×10 -3 , preferably 5×10 -5 ~5×10 -4 , wherein the amount of the polycondensation catalyst is calculated based on the titanium element contained.

8. The method according to claim 1, characterized in that: The polycondensation reaction conditions include: temperature of 200-260° C., pressure of 40-300 Pa (absolute pressure), and time of 1-3 hours; preferably, temperature of 210-250° C., pressure of 50-200 Pa (absolute pressure).

9. An aliphatic polycarbonate obtainable by the process according to any one of claims 1 to 8.

10. The aliphatic polycarbonate according to claim 9, characterized in that: The number average molecular weight of the aliphatic polycarbonate is 2×10 4 ~1.1×10 5 ; The hue b value of the aliphatic polycarbonate is 3-6.

Citation Information

Patent Citations

  • Aliphatic polycarbonate with high molecular weight and preparation method thereof

    CN101643542A

  • Polycarbonate copolymer as well as preparation method and application thereof

    CN113402704A